Diversity, Evenness, and Richness of Mollusc on the Peh Pulo Beach, Blitar Regency - Eva Malahayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Molluscs are one of the most abundant invertebrate animals and live on various substrates. Peh Pulo Beach has a wide coastline, on the edge of the beach there are coral rocks, the sand is white, and the waves are big. Molluscs like to live in coral rock substrates. This research aims to determine the diversity, evenness, and richness of molluscs on Peh Pulo Beach. Sampling was carried out at three different stations using plots measuring 1x1 m which were chosen randomly. Mollusc samples were identified based on morphological characteristics and validated using the WoRMS database. The results of mollusc identification at Peh Pulo Beach showed that there were 37 species belonging to 23 families. They are classified in the classes Gastropods (32 species), Bivalves (3 species), and Polyplacophora (1 species). The diversity of molluscs in the Peh Pulo Beach area is at a moderate level. The evenness of molluscs in Peh Pulo Beach is similar. And the richness of molluscs is at a semi-disturbed level so appropriate management and conservation strategies for the sustainability of molluscs are needed.